Can electron capture tell us the mass of the neutrino?. (22nd March 2016) - Faessler, Amand; Šimkovic, F
Abstract: The neutrino masses are one of the most important open problems in particle physics. Presently major efforts are underway to measure the electron antineutrino-mass by the triton beta decay [1 ] and the effective Majorana neutrino mass by the double beta decay [2 ]. The best way to determine the neutrino mass by electron capture was assumed to be in . The total decay energy of the excited daughter atom has for all excitations the same upper energy limit of the Q -value minus the mass of the electron neutrino. Recently Robertson [3 ] claimed, that the excitation of the two-hole states makes the determination of the neutrino mass by this method practically impossible. But Faessler and Simkovic [4 ] showed, that the influence of the two-hole states is less than 1% near the Q -value, the area relevant for the determination of the neutrino mass. Even weaker are the contributions of the three-hole states [5 ]. The upper end of the calorimetric deexcitation spectrum of Dy is dominated by the highest energy one-hole resonance. With a Lorentzian profile of this resonance one has to fit after including the experimental sensitivity four parameters: (1) the neutrino mass, (2) the Q -value, (3) the width of the resonance and (4) its strength. This contribution discusses the problems of the determination of the neutrino mass by electron capture in . The conclusion of this work is, that the determination of the electron neutrino mass by electron capture in is difficult, but (probably) not impossible.